Analisis Pengaruh Instrumen Moneter Syariah dan Konvensional Terhadap Penyaluran Dana ke Sektor Usaha Mikro Kecil dan Menengah (UMKM) di Indonesia - Masyitha Mutiara Ramadhan; Irfan Syauqi Beik (Department of Islamic Economics, IPB University, 2013)
As monetary authority, Bank Indonesia has developed Islamic Bank Indonesia Certificate (abbreviated as SBIS) as Islamic monetary instrument in addition to Bank Indonesia Certificate (known as SBI), which has become conventional instrument. Both instruments play significant role in the transmission of monetary instrument towards real sector of the economy. Monetary transmission could take place through credit channel or financing channel, from which the fund is used as the source of credit and financing for micro, small and medium enterprises (MSME). This study aims at analyzing the impact of both Islamic and conventional monetary instruments towards MSME financing. Data used in this research is taken from Bank Indonesia, Ministry of Cooperative and SME, and Central Board of Statistics for the period of May 2006 until December 2010. The study employs Vector Auto Regression model, Impulse Response Function technique and Forecast Error Variance Decomposition (FEVD) as its analytical methods. It is found that SBI and SBIS have significant impact towards credit and financing to the MSME. When there is monetary shock, the study finds that MSME financing of Islamic bank could be recovered and stabilized better than MSME credit of conventional bank. FEVD analysis shows that the impact of SBIS towards financing of MSME is bigger than the SBI.